2011
DOI: 10.1080/01419870.2011.535906
|View full text |Cite
|
Sign up to set email alerts
|

The defining moment: children's conceptualization of race and experiences with racial discrimination

Abstract: This paper examines whether children of marginalized racial/ethnic groups have an awareness of race at earlier ages than youth from non-marginalized groups, documents their experiences with racial discrimination, and utilizes a modified racism-related stress model to explore the relationship between perceived racial discrimination and self-esteem. Data were collected for nonHispanic black, non-Hispanic white, and Hispanic children aged 7 -12 using face-to-face interviews (n = 175). The concept of race was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…African American children, for example, typically hear more conversations about race and have more exposure to racial discrimination than White children in the U.S. (e.g., Dulin-Keita, Hannon, Fernandez, & Cockerham, 2011; Hughes, Rodriguez, Smith, Johnson, Stevenson, & Spicer, 2006). These experiences, as well as others (e.g., frequent exposure to racial outgroup members), could lead African Americans to encode race earlier or more robustly than their White peers.…”
Section: Discussionmentioning
confidence: 99%
“…African American children, for example, typically hear more conversations about race and have more exposure to racial discrimination than White children in the U.S. (e.g., Dulin-Keita, Hannon, Fernandez, & Cockerham, 2011; Hughes, Rodriguez, Smith, Johnson, Stevenson, & Spicer, 2006). These experiences, as well as others (e.g., frequent exposure to racial outgroup members), could lead African Americans to encode race earlier or more robustly than their White peers.…”
Section: Discussionmentioning
confidence: 99%
“…The average frequency of discriminatory experiences was calculated by taking the mean of the scores across the 10 items, with higher scores indicating higher levels of perceived discrimination. The scale has been utilized in other studies with adolescents from diverse ethnic backgrounds (Clark, Coleman, & Novak, 2004; Dulin-Keita, Hannon, Fernandez, & Cockerham, 2011) and had good validity ( α = .84).…”
Section: Methodsmentioning
confidence: 99%
“…Leiber and Woodrick (1995) also find that overt racial bias has been replaced with subtle or covert racial discrimination, prejudice, and stereotyping and that youth of color continue to struggle with racial discrimination also as a possible risk factor for low self-esteem (Dulin-Keita et al, 2011). For example, Bridges and Steen (1998) found that probation officers expressed strong beliefs that crimes committed by Black youth were a function of personality and attitudinal traits, whereas crimes by White youth were a result of social Downloaded by [National Sun Yat-Sen University] at 00:26 27 December 2014 environmental factors.…”
Section: Experiences Of Youth Of Colormentioning
confidence: 94%
“…Like other forms of oppression, racism occurs at individual, organizational, and systemic levels, such as with individual probation officers, in individual detention facilities, and across the juvenile justice system (Adams, Bell, & Griffin, 1997;Dulin-Keita, Hannon, Fernandez, & Cockerham, 2011;Young, 1990). Shook and Goodkind (2009) speak to this issue by noting that race differences occur in police handling of youth of color committing minor offenses and that Black youth were 3 times as likely as White youth to be detained.…”
Section: Experiences Of Youth Of Colormentioning
confidence: 98%